المقارنة المورفولوجية والتشريحية لأوراق من أصناف نبات نخيل التمر النامية في منطقة وادي سوف - طواهرية, عبير; مهوات, مارية; طويل, ابتسام (University of Eloued جامعة الوادي, 2023)
This study was carried out in the laboratory of the Faculty of Natural and Life Sciences at the University of Martyr Hama Lakhdar in the valley for the academic year 2021/2022. Where this work aims to study the anatomical comparison for leaves from the date palm of five varieties (Garess, Hamray, White Deggla, Nour Deggla, Tekermist) and cultivated in the area EL-oued (Hassi Khalifa), Through a morphological description (The length and width of the frond, payoff) and anatomical study (the diameter of the clipsome of the leaf, the diameter of the large, medium and small vascular bundles, the diameter of the large fibrous bundle, the number of fibrous bundles between the two large bundles, the number of small and medium vascular bundles between the two large bundles, The area of the primary and secondary wood in the large beam, the thickness of the epidermis and waxy layer and the middle tissue).Through the results obtained, it was found that the Hamraya class achieved the most returns by the number of buds in the palm, Where this breed is distinguished (Hamraya) With the largest number in the medium vascular bundles compared to other varieties, It was also characterized by the smallest thickness of the wax layer, the diameter of the medium vascular bundle as well as the diameter of the large fibrous bundle, while in The rest of the characteristics were average compared to the other varieties.
التنوع البيئي وفيزيولوجيا النبات
Keywords: نخيل التمر ، الصفات المرفولوجية، تشريح الورقة; dates palm (Phoenix dactylifera L); morphological traits; leaf anatomy.